Preparation method and application of semi-crystalline high-transparency multicomponent copolyester

By designing novel branched structures and catalytic systems, and using low-content alkyd copolymerization modification, a semi-crystalline transparent multi-component copolyester was prepared, which solved the shortcomings of PETG materials in terms of cost, recycling and processing performance, and achieved high transparency and easy processing.

CN120988259APending Publication Date: 2025-11-21CHINA RESOURCES PACKAGING MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511198091.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing PETG materials have shortcomings in terms of cost, recycling difficulty, and processing performance. They also have long processing cycles and low melt flow index, which leads to high equipment load and makes it difficult to meet the requirements of high transparency and low cost.

Method used

By employing a novel branched structure design and a main/co-catalyst system, a semi-crystalline transparent multi-component copolyester is prepared through low-content alkyd copolymerization modification. This reduces the material's crystallinity, increases its transparency, lowers its viscosity, and simplifies the processing.

Benefits of technology

It achieves material properties of high transparency, low cost, and easy processing, reduces production costs and processing energy consumption, simplifies drying time, and improves material flowability and recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120988259A_ABST
    Figure CN120988259A_ABST
Patent Text Reader

Abstract

The invention provides a semi-crystalline transparent multicomponent copolyester and a preparation method thereof, and relates to the technical field of polyester synthesis. The preparation method of the semi-crystalline high-transparency multicomponent copolyester comprises the following steps: esterification reaction: mixing terephthalic acid, ethylene glycol, a branching agent, a modified monomer and a main catalyst, and carrying out esterification reaction to obtain an esterification product; and condensation polymerization: mixing the esterification product with a main catalyst, and carrying out condensation polymerization to obtain the semi-crystalline high-transparency multi-component copolyester, the mixture of the esterification reaction and / or the condensation polymerization reaction comprises a cocatalyst. According to the preparation method disclosed by the invention, polyester is subjected to copolymerization modification with relatively low content of alcohol and / or acid modified monomers to obtain the semi-crystalline multicomponent copolyester, and the semi-crystalline multicomponent copolyester is endowed with the advantages of high transparency, high hue, low cost, easiness in processing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of polyester synthesis, and in particular to a semi-crystalline transparent multi-component copolyester and its preparation method. Background Technology

[0002] Materials with high transparency and excellent performance are required in fields such as medical product packaging, sheet and board materials, heat shrink film, and cosmetic packaging. PET (polyethylene terephthalate) is a high-performance and low-cost bulk chemical product, widely used as packaging or sheet and board materials. However, the polymer chains of PET have a certain degree of regularity, causing crystalline and amorphous regions to appear inside the material after processing, resulting in differences in refractive index and affecting the transparency of the material. Introducing new monomers through copolymerization modification to disrupt the regularity of the polymer chains and reduce crystallization can effectively improve the transparency of the material.

[0003] Currently, there are two main routes for modifying PET using acid and alcohol monomers. Acid modification generally refers to improving the transparency of the copolyester by introducing a large amount of diacids with different structures, such as isophthalic acid (IPA), to disrupt the crystallinity of the copolyester. However, the performance improvement is limited, and this type of product has a low market share. Currently, commercially available high-transparency copolyesters are mainly alcohol-modified PET. Most of these are high-performance amorphous copolyesters (PETG) synthesized by copolymerization modification of two PET monomers, namely terephthalic acid (PTA) and ethylene glycol (EG), with a third monomer, 1,4-cyclohexanediol (CHDM) or neopentyl glycol (NPG). Compared to PET, this type of copolyester has higher transparency, excellent hue, light weight, and high mechanical properties, and has largely replaced the fragile and heavy traditional glass material.

[0004] Although PETG is currently widely used in thick-walled containers, heat-shrink films, medical and daily chemical products, and financial cards, there is still room for improvement in terms of cost, recycling, and processing performance. The third monomers used, CHDM and NPG, are expensive, accounting for up to 20% of its composition, resulting in high production costs and difficulties in recycling. PETG is an amorphous polymer, requiring prolonged drying at lower temperatures to prevent particle aggregation before processing. Its glass transition temperature is around 80°C, typically requiring drying at 65°C for about 10 hours, a longer processing cycle compared to semi-crystalline polyesters. Furthermore, PETG has a low melt index, with a viscosity close to 0.8 dL / g, placing a significant load on equipment during processing and molding. Solving these problems is a crucial technological breakthrough for today's highly competitive polyester industry.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] One objective of this invention is to provide a method for preparing a semi-crystalline transparent multi-component copolyester. This method designs a novel copolyester structure and copolymerizes conventional polyesters with various alkyds at low concentrations, endowing the product with advantages such as high transparency, high hue, low cost, and ease of processing.

[0007] The second objective of this invention is to provide a semi-crystalline transparent multi-component copolyester, which is prepared by the above-described preparation method.

[0008] A third objective of this invention is to provide a polyester injection molded product, which is obtained by injection molding the aforementioned crystalline transparent multi-element copolyester.

[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0010] In a first aspect, the present invention provides a method for preparing a semi-crystalline transparent multi-component copolyester, the method comprising:

[0011] Esterification reaction: Terephthalic acid, ethylene glycol, branching agent, modified monomer and main catalyst are mixed and subjected to esterification reaction to obtain esterified product;

[0012] Polycondensation reaction: The esterification product and the main catalyst are mixed and subjected to a polycondensation reaction to obtain the semi-crystalline high-transparency multi-component copolyester;

[0013] Furthermore, the mixture of the esterification reaction and / or polycondensation reaction includes a co-catalyst.

[0014] Furthermore, the branching agent includes any one or a combination of at least two of pyromellitic dianhydride, trimellitic anhydride, pentaerythritol, or glycerol.

[0015] Furthermore, the amount of the branching agent added accounts for 0 to 1000 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

[0016] Furthermore, in the raw materials for the esterification reaction and the polycondensation reaction, the total molar ratio between acidic raw materials and alcoholic raw materials is (1.1 to 1.6):1.

[0017] Furthermore, the modified monomers include acid-modified monomers and / or alcohol-modified monomers.

[0018] Furthermore, in the esterification reaction, the amount of acid-modified monomer added accounts for 0 to 3% of the mass of the final semi-crystalline transparent multi-component copolyester.

[0019] Furthermore, in the esterification reaction, the amount of alcohol-modified monomer added accounts for 0 to 10% of the mass of the final semi-crystalline transparent multi-component copolyester.

[0020] Furthermore, alcohol-modified monomers need to be mixed during the polycondensation reaction.

[0021] Furthermore, in the polycondensation reaction, the amount of alcohol-modified monomer added accounts for 0 to 10% of the mass of the final semi-crystalline transparent multi-component copolyester.

[0022] Furthermore, the acid-modified monomer includes any one or a combination of at least two of furanyl dicarboxylic acid, isophthalic acid, adipic acid, or succinic acid.

[0023] Furthermore, the alcohol-modifying monomer includes any one or a combination of at least two of 1,2-propanediol, diethylene glycol, isosorbide, 1,4-cyclohexanediol, or neopentyl glycol.

[0024] Furthermore, the main catalyst comprises any one or a combination of at least two of aluminum isopropoxide, titanium citrate chelate, germanium dioxide, cobalt acetate, sodium hydroxide, or antimony glycolate.

[0025] Furthermore, the main catalyst also includes a solvent; the solvent includes water and / or ethylene glycol.

[0026] Furthermore, the amount of metal element added in each of the main catalysts accounts for 10 to 1000 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

[0027] Furthermore, the co-catalyst comprises any one or a combination of at least two of tetraethyl orthosilicate, magnesium hydrogen phosphate, or sodium silicate.

[0028] Furthermore, the amount of metal element added or the total amount added in each of the aforementioned co-catalysts accounts for 3 to 100 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

[0029] Furthermore, the esterification reaction also includes a mixed stabilizer.

[0030] Furthermore, the stabilizer includes phosphoric acid and / or phosphate esters.

[0031] Furthermore, the phosphate ester includes triethyl phosphate and / or trimethyl phosphate.

[0032] Furthermore, the amount of the stabilizer added accounts for 20 to 100 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

[0033] Furthermore, the esterification reaction also includes a mixed colorant.

[0034] Furthermore, the amount of the colorant added accounts for 0.1 to 2 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

[0035] Furthermore, the polycondensation reaction also includes mixed antioxidants.

[0036] Furthermore, the antioxidant includes any one or a combination of at least two of hindered phenolic antioxidants, bisphenolic antioxidants, phosphite antioxidants, or phenol-hydrazine complex antioxidants.

[0037] Further, the antioxidant comprises any one or a combination of at least two of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl)phosphite, pentaerythritol diester of bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0038] Furthermore, the amount of antioxidant added accounts for 0 to 1500 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

[0039] Furthermore, the esterification reaction is carried out at a temperature of 220–250°C.

[0040] Furthermore, after the esterification rate of the esterification reaction reaches 85-90%, a polycondensation reaction is carried out.

[0041] Furthermore, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction.

[0042] Furthermore, the temperatures of the pre-condensation reaction and the final condensation reaction are each independently 250–270°C.

[0043] Furthermore, the vacuum degree of the pre-condensation reaction is reduced from atmospheric pressure to below 1 kPa; the vacuum degree of the final condensation reaction is reduced from the vacuum degree of the pre-condensation reaction to below 50 Pa.

[0044] Furthermore, the pre-condensation reaction time is 0.5 to 2.5 hours.

[0045] Furthermore, the viscosity of the product after the polycondensation reaction is 0.65±0.03 dL / g.

[0046] Furthermore, the preparation method of the semi-crystalline transparent multi-component copolyester also includes the following post-processing steps:

[0047] The product obtained from the polycondensation reaction is discharged, granulated, and crystallized to obtain the semi-crystalline high-transparency multi-component copolyester.

[0048] Furthermore, the temperature of the crystallization treatment is 160–190°C.

[0049] Furthermore, the heating rate of the crystallization process is 15–20 °C / h.

[0050] Furthermore, the crystallization process takes 15 to 25 hours.

[0051] In a second aspect, the present invention provides a semi-crystalline transparent multi-component copolyester, wherein the semi-crystalline transparent multi-component copolyester is prepared by the preparation method of the semi-crystalline transparent multi-component copolyester as described in the first aspect.

[0052] Thirdly, the present invention provides a polyester injection molded product, which is obtained by injection molding a semi-crystalline transparent multi-element copolyester as described in the second aspect.

[0053] Fourthly, the present invention provides a method for preparing a polyester injection-molded product as described in the third aspect, the method comprising:

[0054] The semi-crystalline transparent multi-component copolyester is dried and then injection molded to obtain the polyester injection molded product.

[0055] Furthermore, the injection molding temperature is 230–250°C.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] (1) The preparation method of the semi-crystalline transparent multi-component copolyester of the present invention, through the design of a novel branched structure and the development of a main / co-catalytic system, and the copolymerization modification of multi-component monomers with low content of alkyd, reduces the crystallinity of the material, thereby reducing its internal scattering and making the material have high transparency.

[0058] (2) The copolyester obtained by the preparation method of the semi-crystalline transparent multi-element copolyester of the present invention has a low intrinsic viscosity, thereby giving the product high fluidity and reducing the temperature and load during injection molding; and the copolyester obtained by the preparation method of the present invention has semi-crystalline properties, which effectively shortens the drying time before material processing.

[0059] (3) The preparation method of the semi-crystalline transparent multi-component copolyester of the present invention has the characteristics of low cost of modified monomer, low product viscosity, low processing energy consumption and easy recycling, which also reduces the production cost of the material. Attached Figure Description

[0060] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0061] Figure 1 This is a process flow diagram of the method for preparing the polyester injection molded product according to the present invention.

[0062] Figure 2 The image shows the DSC diagram of the semi-crystalline transparent multi-component copolyester provided in Example 1.

[0063] Figure 3 This is a diagram of the rotary drum device used for crystallization processing according to the present invention.

[0064] Figure 4 The images show a comparison of the appearance of the semi-crystalline transparent multi-element copolyester without crystallization treatment, the semi-crystalline transparent multi-element copolyester after crystallization treatment, and the polyester injection molded product. Detailed Implementation

[0065] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0066] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0067] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0068] In a first aspect, the present invention provides a method for preparing a semi-crystalline transparent multi-component copolyester, the method comprising:

[0069] Esterification reaction: Terephthalic acid, ethylene glycol, branching agent, modified monomer and main catalyst are mixed and subjected to esterification reaction to obtain esterified product;

[0070] Polycondensation reaction: The esterification product and the main catalyst are mixed and subjected to a polycondensation reaction to obtain the semi-crystalline high-transparency multi-component copolyester;

[0071] Furthermore, the mixture of the esterification reaction and / or polycondensation reaction includes a co-catalyst.

[0072] The method for preparing the semi-crystalline transparent multi-component copolyester of this invention utilizes a novel branched structure design and a main / co-catalyst system. This synergistic process, using multiple monomers with low alkyd content for copolymerization modification, reduces the material's crystallinity, thereby minimizing internal scattering and resulting in high transparency. The copolyester obtained by this method exhibits low intrinsic viscosity, leading to higher flowability and reduced temperature and load during injection molding. Furthermore, the semi-crystalline nature of the copolyester effectively shortens the drying time before processing. The low cost of modified monomers, low product viscosity, low processing energy consumption, and easy recyclability of the semi-crystalline transparent multi-component copolyester method also contribute to lower production costs.

[0073] In some alternative embodiments, the branching agent includes any one or a combination of at least two of pyromellitic dianhydride (PMDA), trimellitic anhydride (TMA), pentaerythritol (PER), or glycerol (GLY).

[0074] In some optional embodiments, the amount of the branching agent added is 0 to 1000 ppm of the mass of the final semi-crystalline transparent multi-component copolyester, for example, it can be 0.0001 ppm, 0.0005 ppm, 0.001 ppm, 0.005 ppm, 0.01 ppm, 0.05 ppm, 0.1 ppm, 0.5 ppm, 1 ppm, 5 ppm, 10 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 550 ppm, 600 ppm, 650 ppm, 700 ppm, 750 ppm, 800 ppm, 850 ppm, 900 ppm, 950 ppm, or 1000 ppm.

[0075] In some optional embodiments, the total molar ratio between acidic and alcoholic raw materials in the esterification and polycondensation reactions is (1.1 to 1.6):1, for example, it can be 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, etc.

[0076] It should be noted that the acid raw materials refer to: terephthalic acid, acidic substances in branching agents (e.g., pyromellitic dianhydride or trimellitic anhydride), and acid-modified monomers in modified monomers (e.g., furanyl dicarboxylic acid, isophthalic acid, adipic acid, or succinic acid); the alcohol raw materials refer to: ethylene glycol, alcoholic substances in branching agents (e.g., pentaerythritol or glycerol), and alcohol-modified monomers in modified monomers (e.g., 1,2-propanediol, diethylene glycol, isosorbide, 1,4-cyclohexanediol, or neopentyl glycol).

[0077] In some alternative embodiments, the modified monomer includes acid-modified monomers and / or alcohol-modified monomers.

[0078] In some optional embodiments, during the esterification reaction, the amount of the acid-modified monomer added accounts for 0 to 3% of the mass of the final semi-crystalline transparent multi-component copolyester; excluding the lower limit of 0%, for example, it can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, etc.

[0079] In some optional embodiments, during the esterification reaction, the amount of the alcohol-modified monomer added accounts for 0-10% of the mass of the final semi-crystalline transparent multi-component copolyester, for example, 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.

[0080] In some alternative embodiments, alcohol-modified monomers are also mixed during the polycondensation reaction.

[0081] In some optional embodiments, during the polycondensation reaction, the amount of the alcohol-modified monomer added accounts for 0 to 10% of the mass of the final semi-crystalline transparent multi-component copolyester; excluding the lower limit of 0%, for example, it can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.

[0082] In some alternative embodiments, the acid-modifying monomer includes any one or a combination of at least two of furanyl dicarboxylic acid (FDCA), isophthalic acid (IPA), adipic acid (AA), or succinic acid (SA).

[0083] In some alternative embodiments, the alcohol-modifying monomer includes any one or a combination of at least two of 1,2-propanediol (PG), diethylene glycol (DEG), isosorbide (ISB), 1,4-cyclohexanediethanol (CHDM), or neopentyl glycol (NPG).

[0084] In some alternative embodiments, the catalyst for the esterification reaction is the main catalyst.

[0085] In some alternative embodiments, the catalyst for the esterification reaction is a combination of a main catalyst and a co-catalyst.

[0086] In some alternative embodiments, the catalyst for the polycondensation reaction is the main catalyst.

[0087] In some alternative embodiments, the catalyst for the polycondensation reaction is a combination of a main catalyst and a co-catalyst.

[0088] In some alternative embodiments, the main catalyst comprises any one or a combination of at least two of aluminum isopropoxide, titanium citrate chelate, germanium dioxide, cobalt acetate, sodium hydroxide, or antimony glycolate.

[0089] In some preferred embodiments, the main catalyst comprises a combination of at least two of aluminum isopropoxide, titanium citrate chelate, germanium dioxide, cobalt acetate, sodium hydroxide, or antimony glycolate.

[0090] In some preferred embodiments, the main catalyst in the esterification reaction comprises a combination of aluminum propoxide and antimony glycolate; a combination of germanium dioxide and titanium citrate chelate; a combination of aluminum isopropoxide and germanium dioxide; a combination of titanium citrate chelate and antimony glycolate; or a combination of aluminum isopropoxide, germanium dioxide, titanium citrate chelate, and antimony glycolate.

[0091] In some preferred embodiments, the main catalyst in the polycondensation reaction comprises a combination of titanium citrate chelate and cobalt acetate.

[0092] In some alternative embodiments, the main catalyst also includes a solvent.

[0093] In some alternative embodiments, the solvent in the main catalyst includes water and / or ethylene glycol.

[0094] In some optional embodiments, the antimony glycolate needs to be prepared as a solution of antimony glycolate; wherein, the antimony content in the solution of antimony glycolate is 1% to 5%, for example, it can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0095] In some optional embodiments, the sodium hydroxide needs to be prepared as an aqueous solution of sodium hydroxide; wherein the sodium hydroxide content in the aqueous solution of sodium hydroxide is 0-20%, for example, it can be 0.1%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, etc.

[0096] In some optional embodiments, the citrate chelated titanium is prepared as an ethylene glycol solution of citrate chelated titanium; wherein the titanium content in the ethylene glycol solution of citrate chelated titanium is 2-5%, for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0097] In some optional embodiments, the amount of metal element added in each of the main catalysts is 10 to 1000 ppm of the mass of the final semi-crystalline transparent multi-component copolyester, for example, it can be 10 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 550 ppm, 600 ppm, 650 ppm, 700 ppm, 750 ppm, 800 ppm, 850 ppm, 900 ppm, 950 ppm, or 1000 ppm.

[0098] In some alternative embodiments, the cocatalyst comprises any one or a combination of at least two of tetraethyl orthosilicate, magnesium hydrogen phosphate, or sodium silicate.

[0099] In some optional embodiments, the amount of metal element added or the total amount added in each of the co-catalysts accounts for 3 to 100 ppm of the mass of the final semi-crystalline transparent multi-component copolyester, for example, it can be 3 ppm, 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, 30 ppm, 35 ppm, 40 ppm, 45 ppm, 50 ppm, 55 ppm, 60 ppm, 65 ppm, 70 ppm, 75 ppm, 80 ppm, 85 ppm, 90 ppm, 95 ppm, 100 ppm, etc.

[0100] In some alternative embodiments, the esterification reaction also includes a mixed stabilizer.

[0101] In some alternative embodiments, the stabilizer includes phosphoric acid and / or phosphate esters.

[0102] In some alternative embodiments, the phosphate ester includes triethyl phosphate and / or trimethyl phosphate.

[0103] In some optional embodiments, the amount of stabilizer added is 20 to 100 ppm of the mass of the final semi-crystalline transparent multi-component copolyester, for example, it can be 20 ppm, 25 ppm, 30 ppm, 35 ppm, 40 ppm, 45 ppm, 50 ppm, 55 ppm, 60 ppm, 65 ppm, 70 ppm, 75 ppm, 80 ppm, 85 ppm, 90 ppm, 95 ppm, 100 ppm, etc.

[0104] In some optional embodiments, the stabilizer needs to be prepared as an ethylene glycol solution of the stabilizer; wherein the phosphorus content in the ethylene glycol solution of the stabilizer is 1-3%, for example, it can be 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.

[0105] In some alternative embodiments, the esterification reaction further includes mixing with a colorant.

[0106] In some alternative embodiments, the colorant is a common commercially available polyester dye.

[0107] In some optional embodiments, the toner needs to be prepared as an ethylene glycol solution of the toner; wherein, the concentration of the toner in the ethylene glycol solution of the toner is 50 to 300 ppm, for example, it can be 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, etc.

[0108] In some optional embodiments, the amount of the colorant added is 0.1 to 2 ppm of the mass of the final semi-crystalline transparent multi-component copolyester, for example, it can be 0.1 ppm, 0.2 ppm, 0.4 ppm, 0.6 ppm, 0.8 ppm, 1 ppm, 1.2 ppm, 1.4 ppm, 1.6 ppm, 1.8 ppm, 2 ppm, etc.

[0109] In some alternative embodiments, the polycondensation reaction also includes mixed antioxidants.

[0110] In some alternative embodiments, the antioxidant includes any one or a combination of at least two of hindered phenolic antioxidants, bisphenol antioxidants, phosphite antioxidants, or phenol-hydrazine complex antioxidants.

[0111] In some alternative embodiments, the antioxidant includes any one or a combination of at least two of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), tris(2,4-di-tert-butylphenyl)phosphite (antioxidant 168), pentaerythritol diester of bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1425), or N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine (antioxidant 1024).

[0112] In some optional embodiments, the amount of antioxidant added is 0 to 1500 ppm of the mass of the final semi-crystalline transparent multi-component copolyester; for example, it can be 0 ppm, 0.0001 ppm, 0.0005 ppm, 0.001 ppm, 0.005 ppm, 0.01 ppm, 0.05 ppm, 0.1 ppm, 0.5 ppm, 1 ppm, 5 ppm, 10 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 550 ppm, 600 ppm, 650 ppm, 700 ppm, 750 ppm, 800 ppm, 850 ppm, 900 ppm, 950 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, etc.

[0113] In some alternative embodiments, the temperature of the esterification reaction is 220–250°C, for example, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, etc.

[0114] In some alternative embodiments, the esterification reaction is carried out at an esterification rate of 85-90% (e.g., 85%, 86%, 87%, 88%, 89%, 90%, etc.) followed by a polycondensation reaction.

[0115] In some alternative embodiments, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction.

[0116] In some alternative embodiments, the temperatures of the pre-condensation reaction and the final condensation reaction are each independently 250–270°C, for example, 250°C, 255°C, 260°C, 265°C, 270°C, etc.

[0117] In some optional embodiments, the vacuum degree of the pre-condensation reaction is reduced from atmospheric pressure to below 1 kPa; the vacuum degree of the final condensation reaction is reduced from the vacuum degree of the pre-condensation reaction to below 50 Pa.

[0118] In some optional embodiments, the pre-condensation reaction time is 0.5 to 2.5 hours, for example, 0.5 hours, 0.6 hours, 0.7 hours, 0.8 hours, 0.9 hours, 1 hour, 1.2 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.5 hours, etc.

[0119] In some alternative embodiments, the viscosity of the product after the polycondensation reaction is 0.65 ± 0.03 dL / g.

[0120] In some optional embodiments, the polycondensation reaction may further include discharge and pelletizing after completion.

[0121] In some optional embodiments, the polycondensation reaction is further complicated by crystallizing the product obtained from the polycondensation reaction after the reaction is completed.

[0122] In some optional embodiments, the method for preparing the semi-crystalline transparent multi-component copolyester further includes the following post-processing steps:

[0123] The product obtained from the polycondensation reaction is discharged, granulated, and crystallized to obtain the semi-crystalline high-transparency multi-component copolyester.

[0124] In some alternative embodiments, the crystallization treatment temperature is 160–190°C, for example, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, etc.

[0125] In some optional embodiments, the heating rate of the crystallization process is 15-20℃ / h, for example, it can be 15℃ / h, 15.5℃ / h, 16℃ / h, 16.5℃ / h, 17℃ / h, 17.5℃ / h, 18℃ / h, 18.5℃ / h, 19℃ / h, 19.5℃ / h, 20℃ / h, etc.

[0126] In some optional embodiments, the crystallization treatment time is 15 to 25 hours, for example, 15 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 25 hours, etc.

[0127] In some optional embodiments, the crystallization process is a drum heating crystallization process, and the drum speed is determined according to the actual situation, with the aim of preventing particles from sticking together.

[0128] In some optional embodiments, the preparation method of the branched semi-crystalline transparent polyol acid-modified copolyester specifically includes the following steps:

[0129] (1) Terephthalic acid, ethylene glycol, branching agent, acid-modified monomer, alcohol-modified monomer, main catalyst, co-catalyst, stabilizer and colorant are added to a slurry tank and slurry is stirred. The slurry is then introduced into an esterification reactor for esterification reaction to obtain an esterified product with a certain esterification rate.

[0130] (2) Add the main catalyst, co-catalyst, alcohol-modified monomer and antioxidant to the esterification product obtained in step (1), stir and mix, and then introduce the mixture into the polycondensation reactor. First, carry out the pre-polycondensation reaction with low vacuum, and then carry out the final polycondensation reaction with high vacuum to obtain a polycondensation product with a certain viscosity.

[0131] (3) The polycondensation product obtained in step (2) is discharged, granulated and crystallized to obtain the semi-crystalline transparent multi-component copolyester.

[0132] In some alternative implementations, in step (1), the pulping time should be as short as possible, and the pulp should be fed into the esterification reactor as soon as possible after it is mixed evenly.

[0133] In some optional embodiments, in step (1), the esterification rate of the esterification product needs to be detected in real time, and low vacuum prepolymerization can be carried out when it reaches 85-90%.

[0134] In some optional implementations, in step (2), the vacuum level is increased by gradient decompression, and the pressure is reduced to below 1 kPa during the pre-condensation time before entering the high vacuum final condensation stage, where the vacuum level is below 50 Pa.

[0135] In some alternative implementations, in step (2), when the final polycondensation product reaches a certain current and torque value, step (3) can be performed to discharge and pelletize; the current and torque values ​​depend on the specific reactor conditions, and the viscosity needs to be controlled at 0.65±0.03dL / g.

[0136] In a second aspect, the present invention provides a semi-crystalline transparent multi-component copolyester, wherein the semi-crystalline transparent multi-component copolyester is prepared by the preparation method of the semi-crystalline transparent multi-component copolyester as described in the first aspect.

[0137] In some alternative embodiments, the MVR of the semi-crystalline transparent multi-component copolyester is 7 or higher, for example, it can be 7, 7.2, 7.4, 7.6, 7.8, 8, 8.2, 8.4, 8.6, 8.8, 9, 9.2, 9.4, 9.6, 9.8, 10, etc.

[0138] Thirdly, the present invention provides a polyester injection molded product, which is obtained by injection molding a semi-crystalline transparent multi-element copolyester as described in the second aspect.

[0139] In some alternative embodiments, the light transmittance of the polyester injection molded product is 85% or higher, for example, it can be 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, etc.

[0140] In some alternative embodiments, the haze of the polyester injection molded product is below 1.5%, for example, it can be 1.5%, 1.4%, 1.3%, 1.2%, 1%, 0.95%, 0.9%, 0.85%, 0.8%, 0.75%, 0.7%, 0.65%, 0.6%, 0.55%, 0.5%, 0.45%, 0.4%, 0.35%, 0.3%, 0.25%, 0.2%, 0.19%, etc.

[0141] Fourthly, the present invention provides a method for preparing a polyester injection-molded product as described in the third aspect, such as... Figure 1 As shown, the preparation method includes:

[0142] The crystalline transparent multi-component copolyester is dried and then injection molded to obtain the polyester injection molded product.

[0143] In some optional embodiments, the drying temperature is 150-170°C, for example, it can be 150°C, 152°C, 154°C, 156°C, 158°C, 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, etc.

[0144] In some optional embodiments, the drying time is 0.5 to 5 hours, for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.

[0145] In some alternative embodiments, the drying is carried out in a blower drying oven.

[0146] In some alternative embodiments, the injection molding temperature is 230 to 250°C, for example, it can be 230°C, 232°C, 234°C, 236°C, 238°C, 240°C, 242°C, 246°C, 248°C, 250°C, etc.

[0147] In some alternative implementations, the injection molding is performed in an injection molding machine.

[0148] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0149] Example 1

[0150] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester, the preparation method specifically including the following steps (this embodiment is carried out on a 200L polymerization reactor):

[0151] (1) Esterification reaction:

[0152] PTA (58.7 kg), EG (27 kg), alcohol-modified monomers (DEG 140 g, NPG 3.5 kg, ISB 1.4 kg), branching agent (TMA 35 g), main catalyst (aluminum isopropoxide 1.03 g, antimony glycol solution 382 g; the antimony glycol solution is ethylene glycol with an antimony content of 1.4%), co-catalyst (magnesium hydrogen phosphate trihydrate 4.06 g), colorant (0.3 kg), and phosphoric acid solution (280 g; the phosphoric acid solution is ethylene glycol with a phosphoric acid content of 1.5%) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set to 245°C. When the esterification rate reached 90%, the esterified product was obtained.

[0153] (2) Condensation reaction:

[0154] Add the main catalyst (1.27g of citric acid chelated titanium solution and 16.9g of sodium hydroxide aqueous solution; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%; the sodium hydroxide aqueous solution contains 10% sodium hydroxide), the co-catalyst (4.06g of magnesium hydrogen phosphate trihydrate), and antioxidant 1425 (35g) to the esterification reactor containing the esterification product of step (1). After stirring evenly, quickly introduce the mixture into the polycondensation reactor; enter the pre-polycondensation stage at 265℃ and react for 2 hours. During this period, the vacuum degree is reduced from atmospheric pressure to below 1kPa. After the pre-polycondensation is completed, switch the vacuum pump and carry out high vacuum (below 50Pa) final polycondensation at 265℃. When the viscosity reaches 0.65dL / g, discharge and pelletize to obtain the semi-crystalline transparent multi-element copolyester.

[0155] Figure 2 The DSC image of the semi-crystalline transparent multi-component copolyester provided in Example 1; as shown Figure 2 As shown, the sample underwent its first heating, T g1 The temperature was 75.01℃, T m1 The temperature was 231.82. After cooling to 0℃, it was heated a second time. g2 The temperature was 79.36℃, T m2 The temperature was 229.96℃, and cold crystallization peaks appeared around 177℃ in both heating processes. Due to the influence of the thermal history during the first heating, the T of the test sample was... g and T m All data are based on the data from the second heating process.

[0156] Example 2

[0157] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester, the preparation method specifically including the following steps (this embodiment is carried out on a 200L polymerization reactor):

[0158] (1) Esterification reaction:

[0159] PTA (58.2 kg), EG (29.5 kg), alcohol-modified monomers (DEG 1.36 kg, PG 109 g, CHDM 4.2 kg), branching agent (PMDA 20.5 g), main catalyst (germanium dioxide 5.11 g, citric acid chelated titanium solution 17.5 g, ethylene glycol antimony solution 382 g; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%; the solvent of the ethylene glycol antimony solution is ethylene glycol, and the antimony content is 1.4%), colorant (0.3 kg), and phosphoric acid solution (343 g; the solvent of the phosphoric acid solution is ethylene glycol, and the phosphoric acid content is 1.5%) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set at 235°C. When the esterification rate reached 85%, the esterified product was obtained.

[0160] (2) Condensation reaction:

[0161] Add the main catalyst (1.92g cobalt acetate, 8.75g citric acid chelated titanium solution; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%), co-catalyst (3.38g sodium silicate), antioxidant 1010 (23.3g) and antioxidant 168 (46.7g) to the esterification reactor containing the esterification product of step (1). After stirring evenly, quickly introduce the esterified product into the polycondensation reactor and react for 1 hour at 265°C in the pre-polycondensation stage. During this period, the vacuum degree is reduced from atmospheric pressure to below 1kPa. After the pre-polycondensation is completed, switch the vacuum pump and perform high vacuum (below 50Pa) final polycondensation at 265°C. When the viscosity reaches 0.65dL / g, discharge and pelletize to obtain the semi-crystalline transparent multi-element copolyester.

[0162] Example 3

[0163] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester, the preparation method specifically including the following steps (this embodiment is carried out on a 200L polymerization reactor):

[0164] (1) Esterification reaction:

[0165] PTA (58.2 kg), EG (27.5 kg), alcohol-modified monomers (PG 109 g, NPG 1.4 kg, CHDM 2.5 kg), branching agent (PER 12.2 g), main catalyst (aluminum isopropoxide 1.03 g, germanium dioxide 5.11 g, citrate chelated titanium solution 1.27 g, ethylene glycol antimony solution 382 g; the solvent of the citrate chelated titanium solution is ethylene glycol, and the titanium content is 2%; the solvent of the ethylene glycol antimony solution is ethylene glycol, and the antimony content is 1.4%), colorant (0.3 kg), and triethyl phosphate solution (182 g; the solvent of the triethyl phosphate solution is ethylene glycol, and the triethyl phosphate content is 1%) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set at 235℃. When the esterification rate reached 90%, the esterified product was obtained.

[0166] (2) Condensation reaction:

[0167] Add the main catalyst (1.27g of citric acid chelated titanium solution; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%), the co-catalyst (5.23g of tetraethyl orthosilicate), and the antioxidant 1076 (35g) to the esterification reactor containing the esterification product of step (1). After stirring evenly, quickly introduce the mixture into the polycondensation reactor. Enter the pre-polycondensation stage at 265°C and react for 1 hour, during which the vacuum degree is reduced from atmospheric pressure gradient to below 1 kPa. After the pre-polycondensation is completed, switch the vacuum pump and carry out high vacuum (below 50 Pa) final polycondensation at 270°C. When the viscosity reaches 0.65 dL / g, discharge and pelletize to obtain the semi-crystalline transparent multi-element copolyester.

[0168] Example 4

[0169] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester, the preparation method specifically including the following steps (this embodiment is carried out on a 200L polymerization reactor):

[0170] (1) Esterification reaction:

[0171] PTA (58.2 kg), EG (30 kg), alcohol-modified monomers (ISB 1.0 kg, PG 2.3 kg), branching agent (GLY 20.5 g), main catalyst (citric acid chelated titanium solution 17.5 g, ethylene glycol antimony solution 382 g; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%; the solvent of the ethylene glycol antimony solution is ethylene glycol, and the antimony content is 1.4%), colorant (0.23 kg), and trimethyl phosphate solution (155 g; the solvent of the trimethyl phosphate solution is ethylene glycol, and the trimethyl phosphate content is 1%) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set to 240℃. When the esterification rate reached 85%, the esterified product was obtained.

[0172] (2) Condensation reaction:

[0173] Add the main catalyst (1.92g cobalt acetate, 8.75g citric acid chelated titanium solution; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%), the co-catalyst (4.06g magnesium hydrogen phosphate trihydrate), and antioxidant 1024 (35g) to the esterification reactor containing the esterification product of step (1). After stirring evenly, quickly introduce the esterification product into the polycondensation reactor and react for 1 hour at 265°C in the pre-polycondensation stage, during which the vacuum degree is reduced from atmospheric pressure gradient to below 1kPa. After the pre-polycondensation is completed, switch the vacuum pump and carry out high vacuum (below 50Pa) final polycondensation at 265°C. When the viscosity reaches 0.65dL / g, discharge and pelletize to obtain the semi-crystalline transparent multi-element copolyester.

[0174] Example 5

[0175] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester, the preparation method specifically including the following steps (this embodiment is carried out on a 200L polymerization reactor):

[0176] (1) Esterification reaction:

[0177] PTA (56.5 kg), EG (27 kg), acid-modified monomers (IPA 0.98 kg, AA 1.32 kg), alcohol-modified monomers (NPG 1.5 kg), branching agent (TMA 17 g), main catalyst (aluminum isopropoxide 1.03 g, citrate chelated titanium solution 2.5 g; the solvent of the citrate chelated titanium solution is ethylene glycol, and the titanium content is 2%), co-catalyst (magnesium hydrogen phosphate trihydrate 4.06 g), colorant (0.3 kg), and phosphoric acid solution (280 g; the solvent of the phosphoric acid solution is ethylene glycol, and the phosphoric acid content is 1.5%) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set to 245℃. When the esterification rate reached 90%, the esterified product was obtained.

[0178] (2) Condensation reaction:

[0179] Add the main catalyst (1.27g of citric acid chelated titanium solution and 16.9g of sodium hydroxide aqueous solution; the solvent of the citric acid chelated titanium solution is ethylene glycol and the titanium content is 2%; the sodium hydroxide aqueous solution has a sodium hydroxide content of 10%), alcohol-modified monomer (ISB 1.4kg) and antioxidant 1425 (35g) to the esterification reactor containing the esterification product of step (1). After stirring evenly, quickly introduce the esterification product into the polycondensation reactor and react for 2 hours at 265°C in the pre-polycondensation stage, during which the vacuum degree is reduced from atmospheric pressure gradient to below 1kPa. After the pre-polycondensation is completed, switch the vacuum pump and carry out high vacuum (below 50Pa) final polycondensation at 265°C. When the viscosity reaches 0.65dL / g, discharge and pelletize to obtain the semi-crystalline transparent multi-element copolyester.

[0180] Example 6

[0181] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester, the preparation method specifically including the following steps (this embodiment is carried out on a 200L polymerization reactor):

[0182] (1) Esterification reaction:

[0183] PTA (57.7 kg), EG (27 kg), acid-modified monomers (FDCA 1.22 kg, SA 1.12 kg), alcohol-modified monomers (CHDM 2.6 kg), branching agent (PMDA 12.2 g), main catalyst (citric acid chelated titanium solution 2.5 g, aluminum isopropoxide 1.03 g, ethylene glycol antimony solution 382 g; the solvent of the citric acid chelated titanium solution is ethylene glycol, and the titanium content is 2%; the solvent of the ethylene glycol antimony solution is ethylene glycol, and the antimony content is 1.4%), co-catalyst (sodium silicate 3.38 g), colorant (0.3 kg), and phosphoric acid solution (280 g; the solvent of the phosphoric acid solution is ethylene glycol, and the phosphoric acid content is 1.5%) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set to 245℃. When the esterification rate reached 90%, the esterified product was obtained.

[0184] (2) Condensation reaction:

[0185] Add the main catalyst (1.27g of citric acid chelated titanium solution and 16.9g of sodium hydroxide aqueous solution; the solvent of the citric acid chelated titanium solution is ethylene glycol and the titanium content is 2%; the sodium hydroxide aqueous solution contains 1% sodium hydroxide), alcohol-modified monomer (1.4kg of ISB), and antioxidant 1425 (35g) to the esterification reactor containing the esterification product of step (1). After stirring evenly, quickly introduce the esterification product into the polycondensation reactor and react for 2 hours at 265°C in the pre-polycondensation stage, during which the vacuum degree is reduced from atmospheric pressure gradient to below 1kPa. After the pre-polycondensation is completed, switch the vacuum pump and carry out high vacuum (below 50Pa) final polycondensation at 265°C. When the viscosity reaches 0.65dL / g, discharge and pelletize to obtain the semi-crystalline transparent multi-element copolyester.

[0186] Example 7

[0187] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester. In step (1), only one alcohol-modified monomer is used, specifically: NPG and ISB are no longer added, the DEG content is increased to 5.04 kg, and the other steps are the same as in Example 1.

[0188] Example 8

[0189] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester. In step (1), only one alcohol-modified monomer is used, specifically: DEG and ISB are no longer added, the NPG content is increased to 5.04 kg, and the other steps are the same as in Example 1.

[0190] Example 9

[0191] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester. In step (1), only one alcohol-modified monomer is used, specifically: DEG and NPG are no longer added, the ISB content is increased to 5.04 kg, and the other steps are the same as in Example 1.

[0192] Example 10

[0193] This embodiment provides a method for preparing a semi-crystalline transparent multi-component copolyester. In step (1), only one main catalyst is used, specifically: aluminum isopropoxide is not added, the content of antimony glycolate solution is increased to 383.08g, and other steps are the same as in Example 1.

[0194] Example 11

[0195] This embodiment provides a method for preparing a semi-crystalline transparent multi-element copolyester. In step (2), only one main catalyst is used, specifically: no sodium hydroxide aqueous solution is added, the content of citric acid chelated titanium solution is increased to 18.17g, and other steps are the same as in Example 1.

[0196] Comparative Example 1

[0197] This comparative example provides a method for preparing a copolyester, the preparation method specifically including the following steps (this comparative example is carried out on a 200L polymerization reactor):

[0198] (1) Esterification reaction:

[0199] PTA (58.7 kg), EG (27 kg), NPG (3.5 kg), ISB (1.4 kg), tetrabutyl titanate (2.54 g), ethylene glycol antimony solution (382 g, the solvent of ethylene glycol antimony solution is ethylene glycol, and the antimony content is 1.4%), colorant (0.3 kg), and phosphoric acid solution (280 g) were added to a slurry tank and stirred for 15 minutes until homogeneous. The esterification temperature was set to 245℃. When the esterification rate reached 90%, the esterified product was obtained.

[0200] (2) Condensation reaction:

[0201] Tetrabutyl titanate (2.54g), ethylene glycol antimony solution (382g, the solvent of ethylene glycol antimony solution is ethylene glycol, the antimony content is 1.4%), and antioxidant 1425 (35g) were added to the esterification kettle containing the esterification product of step (1). After stirring evenly, the mixture was quickly introduced into the polycondensation kettle. The reaction was carried out at 265°C for 2 hours in the pre-polycondensation stage, during which the vacuum degree was reduced from atmospheric pressure to below 1 kPa. After the pre-polycondensation was completed, the vacuum pump was switched, and the final polycondensation was carried out at 265°C under high vacuum (below 50 Pa). When the viscosity reached 0.65 dL / g, the material was discharged and pelletized to obtain the copolyester.

[0202] Comparative Example 2

[0203] This comparative example provides a method for preparing a copolyester. The only difference from Example 1 is that in step (1), no branching agent is added. Specifically, the branching agent TMA is replaced with an equal mass of acid-modified monomer IPA. The other steps are the same as in Example 1.

[0204] Comparative Example 3

[0205] This comparative example provides a method for preparing a copolyester, which differs from Example 1 only in that no cocatalyst is added in steps (1) and (2). Specifically, in step (1), magnesium hydrogen phosphate trihydrate is no longer added, and the content of aluminum isopropoxide is increased to 5.09 g; in step (2), magnesium hydrogen phosphate trihydrate is no longer added, and the content of citrate chelated titanium solution is increased to 5.33 g; the other steps are the same as in Example 1.

[0206] Test Example 1

[0207] Test sample: Semi-crystalline transparent multi-component copolyester provided in Example 1.

[0208] Test method:

[0209] (1) Crystallization treatment: The semi-crystalline transparent multi-component copolyester samples provided in Example 1 were subjected to crystallization treatment to obtain the final product of the semi-crystalline transparent multi-component copolyester. The crystallization treatment was carried out in a 600L solid-state polycondensation drum device (such as...). Figure 3 The process is carried out on the drum (as shown); specifically: approximately 100 kg of each of the above-mentioned uncrystallized samples are added to the drum, heated under normal pressure and sealed, and heated to 180°C at a gradient heating rate of 18°C / h, and crystallized for 20 h to obtain the final product of the semi-crystalline transparent multi-element copolyester, which is then discharged, sealed, and packaged.

[0210] (2) Preparation of polyester injection molded products: The semi-crystalline transparent multi-element copolyester final product obtained after the above crystallization treatment is placed in a forced-air drying oven and dried at 160°C for 4 hours. The injection molding temperature is set to 240°C, and 7mm light-transmitting plate products are processed to obtain the polyester injection molded products of the corresponding embodiments and comparative examples.

[0211] Test results:

[0212] like Figure 4 As shown, the semi-crystalline transparent multi-component copolyester provided in Example 1 (left), the final product of the semi-crystalline transparent multi-component copolyester obtained by crystallization treatment (middle), and the injection-molded 7mm light-transmitting plate product (right).

[0213] Test Example 2

[0214] Test samples: semi-crystalline transparent multi-component copolyesters provided in Examples 1-11, copolyesters provided in Comparative Examples 1-3, and commercially available domestic PETG products.

[0215] Test method:

[0216] (I) Performance testing of the final product of semi-crystalline transparent multi-component copolyester:

[0217] (I-1) Crystallization treatment: The above samples were subjected to crystallization treatment to obtain the semi-crystalline transparent multi-component copolyester final product. The crystallization treatment was carried out in a 600L solid-state polycondensation drum device (e.g., Figure 3 The process is carried out on the drum (as shown); specifically: approximately 100 kg of each of the above-mentioned uncrystallized samples are added to the drum, heated under normal pressure and sealed, and heated to 180°C at a gradient heating rate of 18°C / h, and crystallized for 20 h to obtain the final product of the semi-crystalline transparent multi-element copolyester, which is then discharged, sealed, and packaged.

[0218] (I-2) Test items: L / a / b, MVR, IV, Tg, and Tm; the final product of the semi-crystalline transparent multi-component copolyester was tested using a spectrophotometer, melt flow index meter, and other testing equipment; the melt volume rate test conditions were 230℃ and 2.16kg.

[0219] (II) Performance testing of polyester injection molded products:

[0220] (II-1) Preparation of polyester injection molded products: The semi-crystalline transparent multi-element copolyester final product obtained after the crystallization treatment in (I-1) above was placed in a forced-air drying oven and dried at 160°C for 4 hours. The injection molding temperature was set to 240°C, and 7mm light-transmitting plate products were processed to obtain the polyester injection molded products of the corresponding embodiments and comparative examples.

[0221] (II-2) Testing items: light transmittance, haze, tensile yield strength, tensile elongation at break; polyester injection molded products of the corresponding examples and comparative examples are tested using testing equipment such as universal tensile testing machine, spectrophotometer, melt flow index meter, etc.

[0222] The test results are shown in Table 1 below:

[0223] Table 1

[0224]

[0225]

[0226] As shown in Table 1, the final product of the semi-crystalline transparent multi-component copolyester (I) of this invention, after crystallization treatment, has an IV value of less than 0.664 dL / g, an L value of 75.40–83.53, an a value of -2.11 to -0.81, a b value of -2.79 to 5.50, an MVR value of 7.12 or higher, a Tg value of 73.28℃ or higher, and a Tm value of 212.32℃ or higher. Meanwhile, the polyester injection-molded product (II) has a light transmittance of 79.69% or higher, a haze of less than 3.30%, a tensile yield strength of 57.32 MPa or higher, and a tensile elongation at break of 112.58% or higher. This demonstrates that the novel catalytic system developed in this invention, and the copolyester with a certain branched structure, possess higher optical properties, better appearance, superior mechanical properties, and a higher melt index compared to previously reported typical modified copolyesters. Furthermore, the method described in this invention, through the design of novel branched structures and the development of a main / co-catalytic system, synergistically modifies the material with low-content alkyd by copolymerization of multiple monomers, thereby reducing the material's crystallinity and internal scattering, resulting in high transparency.

[0227] In summary, the method described in this invention, through the design of a novel branched structure and the development of a main / co-catalyst system, synergistically modifies the material with low-content alkyd using multi-component monomers, thereby reducing the material's crystallinity and internal scattering, resulting in high transparency. Furthermore, the lower intrinsic viscosity imparts higher flowability to the product, reducing the temperature and load during injection molding. Simultaneously, the material's semi-crystalline properties effectively shorten the drying time before processing. The low cost of modified monomers, low product viscosity, low processing energy consumption, and easy recyclability also give this material a significant advantage in production costs compared to existing traditional technologies.

[0228] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a semi-crystalline transparent multi-component copolyester, characterized in that, The preparation method of the semi-crystalline high-transparency multi-component copolyester includes: Esterification reaction: Terephthalic acid, ethylene glycol, branching agent, modified monomer and main catalyst are mixed and subjected to esterification reaction to obtain esterified product; Polycondensation reaction: The esterification product and the main catalyst are mixed and subjected to a polycondensation reaction to obtain the semi-crystalline high-transparency multi-component copolyester; Furthermore, the mixture of the esterification reaction and / or polycondensation reaction includes a co-catalyst.

2. The method for preparing the semi-crystalline transparent multi-component copolyester according to claim 1, characterized in that, The branching agent includes any one or a combination of at least two of pyromellitic dianhydride, trimellitic anhydride, pentaerythritol or glycerol. And / or, the amount of the branching agent added is 0 to 1000 ppm of the mass of the final semi-crystalline transparent multi-component copolyester; And / or, in the raw materials for the esterification reaction and the polycondensation reaction, the total molar ratio between acidic raw materials and alcoholic raw materials is (1.1 to 1.6):1; And / or, the modified monomers include acid-modified monomers and / or alcohol-modified monomers; And / or, in the esterification reaction, the amount of acid-modified monomer added accounts for 0 to 3% of the mass of the final semi-crystalline transparent multi-component copolyester; And / or, in the esterification reaction, the amount of alcohol-modified monomer added accounts for 0 to 10% of the mass of the final semi-crystalline transparent multi-component copolyester. And / or, alcohol-modified monomers need to be mixed during the polycondensation reaction; And / or, in the polycondensation reaction, the amount of alcohol-modified monomer added accounts for 0 to 10% of the mass of the final semi-crystalline transparent multi-component copolyester. And / or, the acid-modifying monomer includes any one or a combination of at least two of furanyl dicarboxylic acid, isophthalic acid, adipic acid or succinic acid; And / or, the alcohol-modifying monomer includes any one or a combination of at least two of 1,2-propanediol, diethylene glycol, isosorbide, 1,4-cyclohexanediol, or neopentyl glycol.

3. The method for preparing the semi-crystalline transparent multi-component copolyester according to claim 1, characterized in that, The main catalyst includes any one or a combination of at least two of aluminum isopropoxide, titanium citrate chelate, germanium dioxide, cobalt acetate, sodium hydroxide, or antimony glycolate. And / or, the main catalyst further includes a solvent; the solvent includes water and / or ethylene glycol; And / or, the amount of metal element added in each of the main catalysts accounts for 10 to 1000 ppm of the mass of the final semi-crystalline transparent multi-component copolyester. And / or, the cocatalyst comprises any one or a combination of at least two of tetraethyl orthosilicate, magnesium hydrogen phosphate, or sodium silicate; And / or, the amount of metal element added or the total amount added in each of the aforementioned cocatalysts accounts for 3 to 100 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

4. The method for preparing the semi-crystalline transparent multi-component copolyester according to claim 1, characterized in that, The esterification reaction also includes a mixed stabilizer; And / or, the stabilizer includes phosphoric acid and / or phosphate esters; And / or, the phosphate ester includes triethyl phosphate and / or trimethyl phosphate; And / or, the amount of the stabilizer added is 20 to 100 ppm of the mass of the final semi-crystalline transparent multi-component copolyester; And / or, the esterification reaction further includes a mixed colorant; And / or, the amount of the colorant added is 0.1 to 2 ppm of the mass of the final semi-crystalline transparent multi-component copolyester; And / or, the polycondensation reaction further includes mixed antioxidants; And / or, the antioxidant includes any one or a combination of at least two of hindered phenolic antioxidants, bisphenol antioxidants, phosphite antioxidants, or phenol-hydrazine complex antioxidants; And / or, the antioxidant comprises any one or a combination of at least two of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl)phosphite, pentaerythritol diester of bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine; And / or, the amount of antioxidant added is 0 to 1500 ppm of the mass of the final semi-crystalline transparent multi-component copolyester.

5. The method for preparing the semi-crystalline transparent multi-component copolyester according to claim 1, characterized in that, The esterification reaction is carried out at a temperature of 220–250°C. And / or, the esterification rate of the esterification reaction is 85-90% before polycondensation reaction is carried out; And / or, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction; And / or, the temperatures of the pre-condensation reaction and the final condensation reaction are each independently 250–270°C; And / or, the vacuum degree of the pre-condensation reaction is reduced from atmospheric pressure to below 1 kPa; the vacuum degree of the final condensation reaction is reduced from the vacuum degree of the pre-condensation reaction to below 50 Pa; And / or, the pre-condensation reaction time is 0.5 to 2.5 h; And / or, the viscosity of the product after the polycondensation reaction is 0.65±0.03 dL / g.

6. The method for preparing the semi-crystalline transparent multi-component copolyester according to claim 1, characterized in that, The preparation method further includes the following post-processing steps: discharging the product obtained from the polycondensation reaction, granulating it, and crystallizing it to obtain the semi-crystalline high-transparency multi-component copolyester.

7. The method for preparing the semi-crystalline transparent multi-component copolyester according to claim 6, characterized in that, The temperature for the crystallization treatment is 160–190°C; And / or, the heating rate of the crystallization treatment is 15-20°C / h; And / or, the crystallization treatment time is 15 to 25 hours.

8. A semi-crystalline transparent multi-component copolyester, characterized in that, The semi-crystalline transparent multi-component copolyester is prepared by the preparation method of the semi-crystalline transparent multi-component copolyester according to any one of claims 1 to 7.

9. A polyester injection molded product, characterized in that, The polyester injection molded product is obtained by injection molding the semi-crystalline transparent multi-component copolyester as described in claim 8.

10. A method for preparing a polyester injection-molded product according to claim 9, characterized in that, The preparation method includes: The semi-crystalline transparent multi-component copolyester is dried and then injection molded to obtain the polyester injection molded product. And / or, the injection molding temperature is 230–250°C.

Citation Information

Cited By

  • High-toughness anti-ultraviolet polyester material for manufacturing vehicle film and preparation method of high-toughness anti-ultraviolet polyester material

    CN121628315A

  • A high-toughness UV-resistant polyester material for automotive film manufacturing and its preparation method

    CN121628315B